2016
DOI: 10.1038/jp.2016.126
|View full text |Cite
|
Sign up to set email alerts
|

The state of point-of-care ultrasonography use and training in neonatal–perinatal medicine and pediatric critical care medicine fellowship programs

Abstract: Both NPM and PCCM fellowship programs believe in the benefits of POCUS and that their physicians should receive the necessary training. Compared with PCCM, NPM fellowships programs have less access to POCUS machines and less frequently use POCUS and train their fellows and attendings. There remain significant barriers to utilization of POCUS, especially in NPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
2
41
0
3
Order By: Relevance
“…These time savings are probably most realized by POCUS, though a recent survey of neonatal-perinatal medicine fellowship directors suggests a lack of access to US machines in many units in the United States. 4 Saul et al described their experience using US for ETT, umbilical line, and peripherally inserted central line positions with a mean scan time of 7 minutes and less, and with > 90% successful identification rates for all examinations. 18 The benefits of US in regard to minimal patient manipulation and lack of radiation exposure warrants further investigation even if the time needed for the examination is ultimately similar to XR.…”
Section: Discussionmentioning
confidence: 99%
“…These time savings are probably most realized by POCUS, though a recent survey of neonatal-perinatal medicine fellowship directors suggests a lack of access to US machines in many units in the United States. 4 Saul et al described their experience using US for ETT, umbilical line, and peripherally inserted central line positions with a mean scan time of 7 minutes and less, and with > 90% successful identification rates for all examinations. 18 The benefits of US in regard to minimal patient manipulation and lack of radiation exposure warrants further investigation even if the time needed for the examination is ultimately similar to XR.…”
Section: Discussionmentioning
confidence: 99%
“…Several impediments for the adoption of point‐of‐care sonography in the NICU have been identified. A recent survey of neonatal‐perinatal medicine and pediatric critical care medicine fellowship programs across the United States suggested that the lack of ultrasound equipment and funding sources were significant obstacles . Another major barrier identified in this study was the lack of trained ultrasound personnel to instruct fellows and faculty in ultrasound scanning techniques.…”
Section: Obstacles For Adoption Of Bedside Sonography In Neonatologymentioning
confidence: 90%
“…A recent survey of neonatalperinatal medicine and pediatric critical care medicine fellowship programs across the United States suggested that the lack of ultrasound equipment and funding sources were significant obstacles. 8 Another major barrier identified in this study was the lack of trained ultrasound personnel to instruct fellows and faculty in ultrasound scanning techniques. Somewhat surprisingly, legal concerns over point-of-care sonography in the NICU was not a chief concern, which is consistent with a recent analysis of a noteworthy legal database in the United States that suggested point-of-care sonography use and interpretation is not a substantial source of lawsuits against neonatologists and pediatric subspecialists.…”
Section: Obstacles For Adoption Of Bedside Sonography In Neonatologymentioning
confidence: 98%
See 2 more Smart Citations